Sustainable Natural Resource Management for Achieving Human Welfare: An Islamic Economic Framework - Burhanudin, Buang; Damayanti Rusmana, Fenny; Sekhruri, Sekhruri (Tinta Emas Institute, 2024)
This research is motivated by the need for special attention to natural resource management amid the ongoing environmental degradation in the world. The objective of this study is to explore the management of natural resources for the creation of human welfare from the perspective of Islamic economics. The research employs a qualitative methodology. The findings indicate that the preservation of natural resources must align with the teachings of Islam as outlined in the Quran and Sunnah. As citizens of Indonesia, the community is obliged to comply with existing regulations in managing available natural resources. Any party that violates these regulations and causes environmental damage will face criminal sanctions commensurate with the offenses committed. The community can utilize natural resources such as marine resources, water, wind, flora, vegetation, and fauna by allocating them to various sectors in order to obtain compensation, provided that the sustainability of these resources is maintained and excessive exploitation is prevented.